Mapping The Potential Creative Tourism Based Community to Build Creative Experience in Gianyar Regency - Ni Nyoman Sri Wisudawati; Putu Ratna Juwita Sari; Ni Wayan Widhiasthini (Universitas Andalas, 2023)
Gianyar regency has a diverse culture and crafts as one of authentic tourism attraction. This study aims to map the creative tourism potential in accordance with the distinction of the artisan village in Gianyar regency. This study solely examined the tourism potential of 14 creative village that had been identified by the government tourism office have creative potential to support promote Gianyar district as a World Craft City in 2023. In this study, a qualitative approach, checklist of observations was also made in each creative village along with interviews with informants from the Gianyar Regency Tourism Office and village head. Each village’s uniqueness and characteristics can be displayed by the development of creative ideas in packaging tourism potential as attractiveness and also other potential to support the main characteristic of the village to create branding of each village. Gianyar needs to market its tourist villages because the tourism potential of many of the villages is essentially comparable, so branding is necessary to each village to create their own identity and have competitiveness. Mapping of natural, cultural and arts made possibilities can be used to ascertain a village’s identity. Based on finding from 14 creative villages in Gianyar regency, it is possible to focus on expanding tourism potential in general while also creating creative tourism such as: Development of a Creative Tourism Village based on the crafts Industry, Development of Gastronomy-based Creative Tourism Villages, Development of a creative tourism village based on performing arts, Development of Nature-based Creative Tourism Villages.